KEAKTIFAN BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT KELAS V SD NEGERI KUALA TRANG - Dazrullisa; Dian Kristanti; Yuliana (LPPM Universitas Cipta Mandiri, 2025)
This study aims to describe student learning activity through the implementation of the Teams Games Tournament learning model on the theme of our friend's environment in class V of Kuala Trang State Elementary School. The type of research used is descriptive research with a qualitative approach. The subjects in this study were one teacher of class V of Kuala Trang State Elementary School. The data collection techniques used in this study were observation, interviews and documentation. The conclusion of this study is that the implementation of the Teams Games Tournament learning model on the theme of our friend's environment in class V of Kuala Trang State Elementary School can increase student activity where the level of activity is very good in the learning, with a very good category. In this case, students are already active in the learning process such as listening to the teacher when the teacher explains the material, asking questions if they find material that they do not understand, writing conclusions from the teacher's explanation, paying attention, discussing, student readiness, student courage, and solving problems.